Design, fabrication, and test of a parallel-coupled slow-wave high-gradient structure for short input power pulses - Weihang Gu; Hao Zha; Jiaru Shi; Yuliang Jiang; Xiancai Lin; Focheng Liu; Jian Gao; An Li; Fangjun Hu; Qingzhu Li; Qiang Gao; Huaibi Chen (Physical Review Accelerators and Beams)
Tsinghua University has designed an X-band (11.424 GHz) slow-wave parallel-coupled ten-cell standing-wave accelerator structure, operated it at a high gradient with 40-ns-long rf pulses. Unexpected bead-pull results were observed during the cold testing, which we attribute to intercavity coupling. To explain these results, a multicell coupling circuit model was developed and used to analyze the data. High-power testing was conducted on the TPOT-X platform, achieving a highest gradient of 130  MV/m after 1.1×10^{7} conditioning pulses. Compared to conventional multicavity high-gradient structures, the distributed power feeding system offers a shorter conditioning period and demonstrates the potential to achieve higher accelerating gradients under short-pulse operation.